Evidence of traditional Chinese medicine for treating type 2 diabetes mellitus: from molecular mechanisms to clinical efficacy - Yadong Ni; Xianglong Wu; Wenhui Yao; Yuna Zhang; Jie Chen; Xuansheng Ding (Pharmaceutical Biology)
Context The global prevalence of type 2 diabetes mellitus (T2DM) has increased significantly in recent decades. Despite numerous studies and systematic reviews, there is a gap in comprehensive and up-to-date evaluations in this rapidly evolving field.Objective This review provides a comprehensive and current overview of the efficacy of Traditional Chinese Medicine (TCM) in treating T2DM.Methods A systematic review was conducted using PubMed, Web of Science, Wanfang Data, CNKI, and Medline databases, with a search timeframe extending up to November 2023. The search strategy involved a combination of subject terms and free words in English, including ‘Diabetes,’ ‘Traditional Chinese Medicine,’ ‘TCM,’ ‘Hypoglycemic Effect,’ ‘Clinical Trial,’ and ‘Randomized Controlled Trial.’ The studies were rigorously screened by two investigators, with a third investigator reviewing and approving the final selection based on inclusion and exclusion criteria.Results A total of 108 relevant papers were systematically reviewed. The findings suggest that TCMs not only demonstrate clinical efficacy comparable to existing Western medications in managing hypoglycemia but also offer fewer adverse effects and a multitarget therapeutic approach. Five main biological mechanisms through which TCM treats diabetes were identified: improving glucose transport and utilization, improving glycogen metabolism, promoting GLP-1 release, protecting pancreatic islets from damage, and improving intestinal flora.Conclusions TCM has demonstrated significant protective effects against diabetes and presents a viable option for the prevention and treatment of T2DM. These findings support the further exploration and integration of TCM into broader diabetes management strategies.